Demonstration of public participation and communication through social media in the network society within Shanghai. Issue 3 (May 2018) - Zhao, Miaoxi; Lin, Yanliu; Derudder, Ben
The rapid development of information and communication technology has led to the Internet and social media becoming a vital platform for public participation in China. The present research sought to understand the complexity of participation in the network society by taking the cancellation of the number 55 bus route in Shanghai as a case study. Both qualitative and quantitative research methods were used to analyze data from a leading social networking site in China. An analysis of participation patterns led to an understanding of the main characteristics of public participation in the network society, and a statistical analysis of the network revealed the features of elite participants in the planning adjustment. A qualitative approach was also used to explore the communication process, which was influenced by Chinese social capital— guanxi . The case study revealed an uneven pattern of public participation in the network society, and suggestions are provided to enhance fairness and effectiveness in this process.